A LITERATURE REVIEW OF THE RELATIONSHIP BETWEEN LIFESTYLE AND THE INCIDENCE OF HYPERTENSION IN KENDARI CITY - Pongsapan, Theoly; Tosepu, Ramadhan ((Jurnal Ilmiah Mahasiswa Kesehatan Masyarakat), 2024)
Hypertension is caused by lifestyle such as unhealthy eating patterns, smoking, rarely exercise, and stress. People who are exposed to an unhealthy lifestyle for a long time tend to have unstable health. This instability in health will result in stress. Long enough stress will cause blood vessels to narrow, causing hypertension. In addition, the older a person gets, the higher a person's risk of suffering from hypertension. This research aimed to determine the factors related to the incidence of hypertension in the community in Kendari City. The method used in writing this literature review began with selecting a topic and then determining keywords for journal searches. Several efforts could be made to prevent hypertension in Kendari City. The community is expected to avoid risk factors that can cause hypertension. Also, the community is suggested to always participate in socialization regarding the impact of hypertension, pay attention to diet such as reducing consumption of instant food to keep blood pressure balanced, limit smoking behavior because it causes hypertension, and also do regular physical activity and looking for activities that can reduce stress levels. Keyword: Lifestyle, smoking, rarely exercise, stress, the incidence of hypertension